NEW TRENDS IN HUMANITARIAN COOPERATION IN THE CONTEXT OF "GREATER EURASIA - S. A. Zhasuzakov (Современная наука и инновации)
The dynamic development of Eurasian integration processes confirms the strategic foresight and prospects of the Eurasian idea, voiced by the President of Kazakhstan N. A. Nazarbayev at the Lomonosov Moscow state University twenty-five years ago. This idea continued the logic of the historical development of Eurasia and testified to a new stage of integration processes.